Infertility and the Endometrium - Lois A. Salamonsen; Evdokia Dimitriadis (IMR Press, 2022)
Background: A couple's infertility can originate from the male and/or the female. In women, the uterus provides the site where the maternal-fetal interface is established and maintained. Final blastocyst development occurs within the uterine cavity, then the blastocyst must attach to and implant into the endometrium (the inner uterine surface), via its outermost trophectodermal cells. Beneath the epithelium, these differentiate into syncytial trophoblast and invasive trophoblast - the latter progress through the endometrium to invade the spiral arteries converting them to the flaccid blood sacs of the placenta. Therefore, the endometrium plays a critical role in establishment of pregnancy. Objectives: To critically examine current knowledge of endometrial preparation for blastocyst implantation and placental development at the cellular and molecular level and to evaluate measures to improve implantation success. Mechanism: Literature searching by leading experts in the field. Findings: A wealth of new knowledge resulting from 'omics' technologies and new functional models has greatly enhanced our knowledge, but this information is yet to be translated into enhanced outcomes. Conclusions: The endometrium remains the 'black box' of infertility. Extensive trials do not support current adjuvant therapies as being better than placebo while effectively timed testing for endometrial preparedness for implantation is still urgently needed.